Analisis Perubahan Kurikulum Pendidikan di Sekolah MAPN 4 Medan - Annisa Miranda; Nurul Tiana Hasri; Miftahul Jannah (Asosiasi Riset Ilmu Pendidikan Indonesia, 2025)
The purpose of this study was to investigate how Madrasah Aliyah Negeri Preparatory 4 (MAPN 4) Medan implemented curriculum adjustments in preparation for the preservation of the Independent Curriculum. Data were collected through interviews with teacher representatives, activity documentation, and analysis of interview transcript themes and mentoring materials using qualitative descriptive methodology. Based on these findings, MAPN 4 Medan has adopted curriculum modifications progressively and methodically, starting with the School Level Curriculum (KTSP), continuing to the 2013 Curriculum, and ending with the Independent Curriculum. The role of teachers is very central to the successful implementation of this curriculum, both as learning facilitators, developers of open modules, and implementers of formative evaluations. Despite facing various challenges such as understanding learning concepts and time constraints, most teachers showed high enthusiasm and readiness to adapt, supported by internal training and support. Meanwhile, students showed active involvement in project-based and thematic learning, although there were still errors in adaptability. Overall, this study concludes that the implementation of the Independent Curriculum at MAPN 4 Medan reflects the institution's readiness to incorporate 21st-century skills and character values into the educational process, in line with strengthening the Pancasila Student Profile.